Three new combinations in Gloeocantharellus (Gomphales, Agaricomycetes) from Mexico based on molecular evidence - González-Ávila, Astrid; Ramírez-Martínez, César Ramiro; Alvarado-Sizzo, Hernán; Valenzuela, Ricardo; Luna-Vega, Isolda (Phytotaxa, 2020)
In this study, we included for the first time three Mexican Gomphaceae species in a molecular phylogeny. These species were described as members of the genus Gomphus, despite their tropical and subtropical habitat. We undertook a molecular analysis using the atp6 and SSU mitochondrial loci and nuclear ribosomal LSU. Our analysis showed that the three species studied are better included as members of Gloeocantharellus. In this study, we are suggesting three new combinations: Gloeocantharellus albidocarneus, G. calakmulensis and G. pleurobrunnescens.